Politik Islam Masa Orde Baru dan Masa Reformasi - Adim, Abd.; Hasan, Ahmadi; Umar, Masyithah; Khasyi'in, Nuril (PT. Sharia Journal and Education Center, 2024)
Abstract This research discusses the correlation between Islamic politics during the New Order and Reformation era, how the Islamic movement influenced politics in Indonesia, and how these two political concepts influenced each other and contributed to the development and growth of the country even though there was political upheaval during the transition period from the New Order to the Reformation era. Islam first taught politics as a scientific discipline with the science of siyasah which consists of political concepts and principles in Islam such as Siyasah Dusturiyyah, Siyasah Dauliyyah, Siyasah Maliyyah, Siyasah Amiriyah, Siyasah Khalifah, and Siyasah Imamah. In general, Islamic politics has a very large movement, but when it was faced with government politics, Islamic politics is not able to dominate movements on the political stage in Indonesia. However, some of the Islamic values ​​can be embedded in the development of the country, even on a small scale as a reflection that the majority of the population is Muslim. Muslim who has always been involved in politics in Indonesia from time to time. Keywords: Politics, Islam, New Order Era, and Reformation Era Abstrak Penelitian ini membahas tentang korelasi antara politik Islam pada masa Orde Baru dan Reformasi, bagaimana pergerakan Islam pada perpolitikan di Indonesia, serta bagaimana kedua konsep politik tersebut saling mempengaruhi dan berkontribusi terhadap perkembangan dan pertumbuhan negara meskipun terjadi pergolakan politik di masa transisi yaitu politik di masa Orde Baru menuju masa Reformasi. Sedangkan Islam terlebih dahulu mengajarkan tentang politik sebagai sebuah disiplin ilmu yaitu ilmu siyasah yang terdiri dari konsep dan prinsip politik dalam Islam seperti Siyasah Dusturiyyah, Siyasah Dauliyyah,, Siyasah Maliyyah, Siyasah Amiriyah, Siyasah Khalifah, dan Siyasah Imamah. Secara garis besar politik Islam sangat besar pergerakannya di Indonesia, namun jika dihadapkan dengan politik pemerintah, politik Islam tidak mampu mendominasi pergerakan di panggung perpolitikan di Indonesia, meskipun demikian sebagian dari nilai-nilai Islam bisa ditanamkan pada pembangunan negeri, walaupun dalam skala kecil sebagai cerminan bahwa mayoritas penduduk Islam beragama Islam yang selalu membersamai perpolitikan di Indonesia dari masa ke masa. Kata kunci: Politik, Islam, Orde Baru, dan Reformasi